Destination : nation's tribute to Deendayal Upadhyaya - Upadhyaya, Deendayal, 1916-1968; Raje, Sudhakar, 1925- (Deendayal Research Institute, 1978)
On the life and activities of Deendayal Upadhyaya, 1916-1968, Indian political leader.